Performance comparison of clustering and thresholding algorithms for tuberculosis bacilli segmentation. - Mohammad Khusairi, Osman; Mohd Yusoff, Mashor, Prof. Dr.; Hasnan, Jaafar (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/